Evaluation the efficacy of Leea indica leaves aqueous extract against nephrotoxicity induced by Diethylnitrosamine (DEN) in male rats - Kazam, Mustafa Abd-Alhussein; Alsalame , Heba A. Abd-Alsalam (Journal of Kerbala for Agricultural Sciences, 2023)
The aim of this study is to find out the quality of the aqueous extract of leea indica leaves in protecting kidney tissues from oxidative stress caused by DEN. Forty adult males were randomly assigned in four equal sets (ten animals per set), the (G1) They were given 1 ml of normal water, a control set was returned, and the G2 given200 mg/kg of DEN two days , while the G3 given 60 mg/kg of leea indica leaves, while the animals of thegiven G4 200 mg/kg of DEN. And 60 mg/kg of L.indica extract. FINDINGS When the albino rat was dosed with leea indica aqueous extract, the kidney damage induced by DEN was significantly decreased. The extract worked to mitigate kidney damage caused by DEN, which was demonstrated in histological examination by atrophy of the renal glomerulus and shrinkage of the glomerulus. Urinary tubules break down with hemorrhage. We conclude from the current study that the aqueous extract of the leaves of the bandicoot berries contributed to the reduction of hepatotoxicity induced by diethyl nitrosamine.